Nonlinear dynamics of a sliding pipe conveying fluid. (August 2018) - Yan, Hao; Dai, Huliang; Ni, Qiao; Wang, Lin; Wang, Yikun
Abstract: In this study, nonlinear analysis on dynamic responses of a sliding fluid conveying pipe with length time-varying is performed in detail. An extended Hamilton's principle is utilized to derive the nonlinear governing equation of motion for the pipe system. Subsequently, effects of flow velocity, sliding rate and two key parameters, e.g. mass ratio and gravity, on dynamic behavior of the pipe are elaborately addressed. The obtained results indicate that the dynamics and stabilities of the pipe system are quite sensitive to the flow velocity, which is dependent on different values of the sliding rate. As the flow velocity is beyond the critical value, flutter occurs and this flutter amplitude of pipe changes with time going on. In addition, it is shown that the pipe becomes easier to lose stability with the increase of the sliding rate, while increasing the mass ratio and gravity of the pipe can enhance its stability.